Understanding the Way in Which Students Contribute to Knowledge Building and Knowledge Claim Critiquing Within a Community of Learners Working in a Computer Supported Learning Environment - Fullick, Patrick (Proceedings of the International Conference on Networked Learning, 2004)
In this paper, the theoretical perspectives used in a study of on line learning are described. Using activity theory as an organising principle, a group of science students were brought together on line to produce a knowledge building community. Using a methodology involving both content analysis and group interviews, the interactions between members of the community were studied, based on ideas drawn from the sociology and philosophy of science. Results from this study suggest that this methodology provides a powerful technique when exploring on line learning, producing deeper meanings from data than would be possible using content analysis alone.